Mahler's voices : expression and irony in the songs and symphonies - Johnson, Julian (Oxford University Press, 2009)
1. Mahler and the Musical Voice. a. The Idea of Voice. b. Songs and Symphonies. c. Orchestral Voices. 2. Calling Forth a Voice. a. Calling Forth. b. Horn Calls, Birdsong and Bell. c. Calling Back. 3. Constructing a Voice. a. Artifice and Invention. b. Des Knaben Wunderhorn. c. The Middle Symphonies. 4. Plural Voices. a. Carnival Humor. b. Irony and Tone. c. Borrowed Voices. 5. Genre and Voice. a. Song. b. Opera. c. Symphony. 6. Ways of Telling. a. Literary Voices. b. Idyll, Dream and Fairytale. c. Narrative Strategies. 7. Vienna, Modernism and Modernity. a. Critical voices. b. Modernist voices.